Detection of Sarcocystis halieti in muscles of raptors from Lithuania - Prakas, Petras; Šukytė, Tautvilė; Juozaitytė-Ngugu, Evelina; Butkauskas, Dalius (Frontiers in Veterinary Science, 2025)
BackgroundThe genus Sarcocystis comprises a diverse group of apicomplexan parasites that infect reptiles, birds, and mammals. They are characterized by the formation of sarcocysts in the muscles of the intermediate host and the development of sporocysts in the intestines of the definitive host. Raptors usually act as definitive hosts for numerous Sarcocystis species; however there is a lack of studies on Sarcocystis in the muscles of raptorial birds. Therefore, we aimed to assess infection rates and identify Sarcocystis species in the muscles of raptors in Lithuania.MethodsMuscle samples from 90 raptors (Accipitriformes, Falconiformes, and Strigiformes) were collected throughout Lithuania and analyzed for Sarcocystis spp. Sarcocysts isolated from fresh methylene blue-stained muscle samples were identified using the internal transcribed spacer region 1 sequence genetic marker.ResultsUnder the light microscope, sarcocysts were detected in 8.9% (8/90) of the raptors examined. Sarcocysts were found in the leg muscles of common buzzards (Buteo buteo), tawny owls (Strix aluco), and a long-eared owl (Asio otus); neck muscles of a Eurasian goshawk (Accipiter gentilis), rough-legged buzzard (Buteo lagopus), and long-eared owl; and thoracic muscles of a rough-legged buzzard. We observed no sarcocysts in the cardiac muscles. Representatives of one Sarcocystis species, S. halieti were molecularly identified in seven birds.ConclusionThis is the first study to report five new intermediate hosts for S. halieti. Further investigations are needed to assess the possible pathogenicity of S. halieti in extra-intestinal organs of raptors.